Three-Dimensional Leukemia Co-Culture System for In Vitro High-Content Metabolomics Screening. (September 2019) - Lu, Xiyuan; Lodi, Alessia; Konopleva, Marina; Tiziani, Stefano
Metabolomics is increasingly applied to investigate different individuals and time-dependent responses to environmental stimuli. Rapid data acquisition and improved detection limits of direct infusion mass spectrometry (DIMS) are paving the way for applications of metabolomics in preclinical screening, opening new opportunities in drug discovery and personalized medicine. Three-dimensional (3D) cell culture systems, which mimic the in vivo cell microenvironment, are well recognized as tissue and organ substitutes. Here, we investigated cell viability and induction of reactive oxygen species (ROS) in stromal cells cultured in various 3D systems as well as the standard monolayer culture to evaluate which system provides the most favorable growing conditions. The selected 3D system was then tested for use in 3D co-culture of leukemia and stromal cells for DIMS-based high-throughput/high-content metabolic drug screens. The NanobioMatrix–poly(ε-caprolactone) (NBM–PCL) scaffold resulted in the lowest ROS production, supported rapid cell proliferation, and was suitable for the 96- and 384-well plate formats. Doxorubicin treatment in leukemia co-cultured with stromal cells induced some unique metabolic responses that drastically differed from those observed in leukemia cells alone. The DIMS results also showed that the drug-induced metabolic modulations in both normal and cancer cells were weakened by co-culturing even at high treatment doses, thereby demonstrating the value of the 3D co-culture high-content metabolic drug screen. In conclusion, we optimized a high sample throughput method for 3D co-culture with a DIMS-based high-content metabolic drug screen and drug development.